2014
DOI: 10.1371/journal.pone.0101927
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Change to Birds over 120 Years Is Not Explained by Thermal Adaptation to Climate Change

Abstract: Changes in morphology have been postulated as one of the responses of animals to global warming, with increasing ambient temperatures leading to decreasing body size. However, the results of previous studies are inconsistent. Problems related to the analyses of trends in body size may be related to the short-term nature of data sets, to the selection of surrogates for body size, to the appropriate models for data analyses, and to the interpretation as morphology may change in response to ecological drivers oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 59 publications
0
32
1
Order By: Relevance
“…Finally, local responses to small‐scale environmental changes might also be important contributors to size changes (Ozgo & Schilthuizen, ). Hence, studies like ours should be complemented by detailed monitoring of phenotypic and environmental change at the local or regional scale (Gardner, Amano, Mackey, et al., ; Salewski et al., ). Preferably, such studies would be replicated across the continent, but unfortunately, long‐term studies in general, and of bird color variation in particular, are rare (but see Karell et al., for an example).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, local responses to small‐scale environmental changes might also be important contributors to size changes (Ozgo & Schilthuizen, ). Hence, studies like ours should be complemented by detailed monitoring of phenotypic and environmental change at the local or regional scale (Gardner, Amano, Mackey, et al., ; Salewski et al., ). Preferably, such studies would be replicated across the continent, but unfortunately, long‐term studies in general, and of bird color variation in particular, are rare (but see Karell et al., for an example).…”
Section: Discussionmentioning
confidence: 99%
“…Potential alternative explanations, in particular for increases in body size, include the selective pressures exerted by extreme climatic events (McKechnie & Wolf, 2010) and changes in migratory behavior (Salewski et al, 2014). Extreme climatic events include heat and cold waves and periods with extreme low or high rainfall (Bailey & Pol, 2016).…”
Section: Temporal Changes In Body Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The few existing studies focusing on temporal change in body size showed contrasting trends between species (Gardner et al 2014a, Salewski et al 2014, but see Gardner et al 2009, Van Buskirk et al 2010) and/ or between sites (Meiri et al 2009, Collins et al 2017). The few existing studies focusing on temporal change in body size showed contrasting trends between species (Gardner et al 2014a, Salewski et al 2014, but see Gardner et al 2009, Van Buskirk et al 2010) and/ or between sites (Meiri et al 2009, Collins et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This disagreement is reinforced by a probable publication bias towards cases exhibiting significant changes (Meiri et al 2009). Moreover, some studies were based on museum data (Salewski et al 2014) and may have been prone to temporal collection and curation biases. Moreover, some studies were based on museum data (Salewski et al 2014) and may have been prone to temporal collection and curation biases.…”
Section: Introductionmentioning
confidence: 99%